Peningkatan Kompetensi Akidah dan Karakter Islami melalui Metode Keteladanan dalam Konsep Al-Walā' wa Al-Barā' - Nisa, Ainun; Kumalla, Ayub; Erlina, Erlina; Kholid, Idham; Ghazi, Fachrul (Paedagogie, 2025)
The phenomenon of weakening faith and declining Islamic character among the younger generation of Muslims in the era of globalization and digitalization indicates that the process of internalizing faith values ​​in education has not been optimal. This condition demands a renewal in faith learning that is not solely oriented towards knowledge but also emphasizes role models as a means of developing students' spirituality and morals. This study aims to explain the values ​​of faith education and Islamic character development through the application of the exemplary method within the concept of Al-Walā’ wa Al-Barā’ as explained in the book Tarbiyatul Aṭfāl by Sheikh Ra’fat Farīz Shalabī. The model used is the exemplary method (uswah hasanah), as this method is considered the most effective in instilling faith values ​​through concrete examples in the behavior, speech, and attitudes of educators that align with Islamic teachings. In the context of Al-Walā’ wa Al-Barā’, this method encompasses two important aspects: fostering loyalty to Allah, the Prophet, and the Muslims (Al-Walā’), and instilling an attitude of avoiding values ​​that conflict with Islam (Al-Barā’). This research uses a descriptive qualitative approach through a literature review, analyzing classical and contemporary Islamic educational texts and literature. The results show that the exemplary method based on the concept of Al-Walā’ wa Al-Barā’ can strengthen understanding of the creed, foster commitment to faith, and shape a resilient Islamic character amidst the moral challenges of the modern era. Keywords: Creed Education, Islamic Character, Exemplary Method, Al-Walā’ wa Al-Barā’, Tarbiyatul Aṭfāl.